(untitled) (Public Sector Economics - submission site, 2023)
Since increases in public pensions are generally related to prices or wages or combinations of them, the impact of inflation on the real value of benefits can often be neglected, especially in the case of indexation to prices. With high and accelerating/ decelerating inflation like that currently prevailing in Hungary, however, this is not the case. (i) With fast inflation of basic necessities, the proportional indexation of benefits in progress devalues the lowest benefits, which have to pay for above-the-average consumption share of these goods. (ii) Annual “lumpy” increases of these benefits entail too high an intra-year drop in the real value of benefits. (iii) With accelerating inflation, the declining real value of delayed initial benefits may incentivise immediate retirement. (iv) With unindexed parameter values (like progressivity bending points), the initial benefits’ structure unintentionally changes.